Mimicking Multiple Whale Whistles-Based Underwater Covert Communication - Hojun Lee; Yongcheol Kim; Seunghawn Seol; Wanjin Kim; Jongmin Ahn; Jaehak Chung (IEEE Access, 2022)
In underwater biomimetic covert communications, multiple whale whistles are mimicked for improving covertness. The conventional mimicking methods suffered from the trade-off between the mimicking performance and the bit error rate (BER). In this paper, we propose a continuous phase-multiple chirp modulation (CP-MCM) and a hybrid orthogonal whistle modulation (HOWM) to improve the BER and the mimicking performance of the biomimetic covert communication with the multiple whistles. The proposed CP-MCM utilizes chirp signals as the carriers of transmission symbols to mimic the frequency contour of the whistles accurately. The proposed HOWM utilizes the conventional OFDM in the overlapping whistle regions to avoid the interferences and the CP-MCM in the nonoverlapping regions to attain the large mimicking performance. Computer simulations and practical ocean experiments demonstrated that the proposed HOWM mimicked the multiple whistles with better BER performance than conventional methods.